2013
DOI: 10.1080/10255842.2012.745857
|View full text |Cite
|
Sign up to set email alerts
|

Computational model for simulation of vascular adaptation following vascular access surgery in haemodialysis patients

Abstract: An important number of surgical procedures for creation of vascular access (VA) in haemodialysis patients still results in non-adequate increase in blood flow (non-maturation). The rise in blood flow in arteriovenous shunts depends on vascular remodelling. Computational tools to predict the outcome of VA surgery would be important in this clinical context. The aim of our investigation was then to develop a 0D/1D computational model of arm vasculature able to simulate vessel wall remodelling and related changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…The results of our clinical and numerical investigations provide evidence that the patient-specific hemodynamic computational models that we used 16,21 are accurate …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The results of our clinical and numerical investigations provide evidence that the patient-specific hemodynamic computational models that we used 16,21 are accurate …”
Section: Discussionmentioning
confidence: 80%
“…In addition, in order to reliably predict changes in BFV several weeks after surgery, the solver embeds a vascular adaptation algorithm 21 calibrated (by setting of model constants, as recently described) 21 using a data set obtained by a previous investigation 26 based on the assumption that changes in blood vessel diameter take place upon changes in BFV to maintain a physiological value of the peak wall shear stress acting on vascular endothelial cells. 21 Brachial and radial artery BFV and diameter of vessels involved in the anastomosis were predicted according to AVF configuration using patient-specific theoretical vascular network models based on preoperative data (demographic and clinical parameters, blood pressure measurements, cardiac output and frequency, blood analysis, and preoperative brachial, radial, and ulnar artery BFV and major arm vessel diameters, as assessed during preoperative US examination). These theoretical models are based on a previously defined 28 network model of artery and vein segments connected on anatomical basis.…”
Section: Hemodynamic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion of patients with unknown etiology are reported in the literature, 16.2% of the elderly Indian Affairs, [12] 5.9% in the United States, 18% in the United Kingdom [13] and, similarly, 14, 8% in Iran. [14] Our finding of 31.7% of cases of unknown etiology may reflect the lack of awareness of the disease, deficiency in early diagnosis and delay in referral before you get to the specialist.…”
Section: Discussionmentioning
confidence: 99%
“…[3,9] They should be made 6 months prior to initiating haemodialysis. [10] If an AVF cannot be created, an AVF graft or venous catheter may be needed [11,12] but they should be avoided [6,13]. The studies showed that the native access presents the best patency (4 to 5 years) and lower rate of reoperation when compared with other accesses [14,15].…”
Section: Introductionmentioning
confidence: 99%